TEACHER’S EFFORTS TO DEVELOP THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH CHILD-FRIENDLY EDUCATION - Suci Muzfirah; Frenky Mubarok; Muasromatul Azizah; Muhammad Afdal (Jurnal Pendidikan Educandum, 2025)
Every human being has various characters, especially children in elementary school. Children aged 7-12 years are in the "golden age", where character begins to form. The character of students seems to have not been implemented well in the school environment, even though it is very important to form a good personality. The purpose of this study is to determine the important role of teachers in developing student character in elementary schools through child-friendly education. This research method uses a descriptive and qualitative approach, to describe, illustrate, and explain the teacher's efforts in developing student characteristics with data collection techniques, observation, and interviews. The results of the study indicate that teachers are good and able to understand the characters that must be applied to students, the role of teachers is quite significant in developing student character through habituation learning activities, school culture, extracurricular activities and the school's vision and mission.